The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1365-2435.1999.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic signals in the life histories of insects: the distribution and abundance of heather psyllids (Strophingia spp.) in the UK

Abstract: Summary1. The population density and age structure of two species of heather psyllid Strophingia ericae and Strophingia cinereae, feeding on Calluna vulgaris and Erica cinerea, respectively, were sampled using standardized methods at locations throughout Britain. Locations were chosen to represent the full latitudinal and altitudinal range of the host plants. 2. The paper explains how spatial variation in thermal environment, insect life-history characteristics and physiology, and plant distribution, interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 23 publications
2
48
0
Order By: Relevance
“…The prediction of the responses of insects to thermal changes is largely based on studies of phytophagous species (i.e. Strathdee & Bale, 1995;Williams & Liebhold, 1995;Hodkinson & Bird, 1998;Hodkinson et al, 1999). Nevertheless, there is no information on the reproductive biology of C. florentinus, a potential pest of Quercus species, which are the main component of the Mediterranean mixed forests.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of the responses of insects to thermal changes is largely based on studies of phytophagous species (i.e. Strathdee & Bale, 1995;Williams & Liebhold, 1995;Hodkinson & Bird, 1998;Hodkinson et al, 1999). Nevertheless, there is no information on the reproductive biology of C. florentinus, a potential pest of Quercus species, which are the main component of the Mediterranean mixed forests.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have examined the importance of climate, host plant phylogeny, and host plant traits in influencing insect assemblage structure (Hairston et al 1960;Hodkinson et al 1999;Novotny et al 2002;Speight et al 1999), the relative influences of two or more factors remain poorly understood. Here, using highly specialized herbivores (plant gallers and leaf miners) to assess the influences of these factors, we found that the factors that best explained leaf miner richness across the climatic gradient included specific leaf area (SLA), foliage thickness and mean annual rainfall, whereas C:N ratio was the most important factor that explained plant galler richness across the climatic gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Given the diversity of invertebrate responses to climate change (e.g., ref. 44), it seems likely that the avian insectivores least affected by climate change will be those with the greatest diversity of suitable prey for egg laying and chick rearing.…”
Section: Discussionmentioning
confidence: 99%